Increase of the Photocatalytic Activity of TiO𝟐 by Carbon and Iron Modifications - Beata Tryba (International Journal of Photoenergy)
Modification of TiO2 by doping of a residue carbon and iron can give enhanced photoactivity of TiO2. Iron adsorbed on the surface of TiO2 can be an electron or hole scavenger and results in the improvement of the separation of free carriers. The presence of carbon can increase the concentration of organic pollutants on the surface of TiO2 facilitating the contact of the reactive species with the organic molecules. Carbon-doped TiO2 can extend the absorption of the light to the visible region and makes the photocatalysts active under visible-light irradiation. It was proved that TiO2 modified by carbon and iron can work in both photocatalysis and photo-Fenton processes, when H2O2 is used, enhancing markedly the rate of the organic compounds decomposition such as phenol, humic acids and dyes. The photocatalytic decomposition of organic compounds on TiO2 modified by iron and carbon is going by the complex reactions of iron with the intermediates, what significantly accelerate the process of their decomposition. The presence of carbon in such photocatalyst retards the inconvenient reaction of OH radicals scavenging by H2O2, which occurs when Fe-TiO2 photocatalyst is used.